Technology Used by Hearing-Impaired Adolescents for Social Inclusion: A Cross-sectional Study - Samina Ashraf; Sayyeda Rabia Basri; Iqra Fatima (Journal of Business and Social Review in Emerging Economies, 2023)
Purpose: Presently hearing-impaired adolescents are not alien to the world and facing social segregation due to limited social skills. The use of ICT is one of the major assistance applicable for the social inclusion of students with hearing impairment (SWHI) by compensating the limited hearing.